EFFECTS OF LEARNING STYLES CRITICAL THINKING ABILITY OF SUBJECTS IN ECONOMY CLASS X SEMESTER KARTIKATAMA METRO HIGH SCHOOL ACADEMIC YEAR 2016/2017 - Ellys Ervyani; Meyta Pritandhari (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
Based on the observations on Economic subjects in class X SMA Kartikatama Metro, there is still many students’ ability to think critically low with 36% of students who achieve a critical criterion, while 64% were reached yet critical criteria. Alternatives to improve students’ critical thinking that takes into account the tendency of learning styles of students through the delivery of material students' learning styles, using the student's learning style is expected to excite students to learn the material presented through multimedia (text, image, audio, video), which is expected to imagination will increase which is in turn will encourage the emergence of students' ability to think. This research is quantitative, with purposive sampling technique that determines the sample with a certain consideration, in order to get the experimental group at X.1 classes totalling 25 students. The group was given a questionnaire to measure the dependent variables were then given a delivery of material by observing the visual learning style as an independent and then given a test to see results from the delivery of material that has been implemented. From the analysis of survey data obtained t count=5.96 while the t-table = 1.71 at the 0.05 level of significance and the t-table 2.50 at significance level of 0.01 or 1% thus t count> t-table this means hypothesis is accepted, and the results of this study concluded that: learning styles can improve critical thinking skills on the subject of growth of economy , Evidenced by the average of the initial measurement questionnaire before learning 60 and the average test after the delivery of content by 85.02. On average students are in the interval from 0 81-100 students increased categorized as very critical as 6 students, average students in the interval 61-80 with critical category of 6 students increased by 17 students, average students are in 21-40 interval with a critical enough category of 19 students has decreased by 2 students